2002
DOI: 10.1016/s0017-9310(02)00105-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and phase change during picosecond laser ablation of nickel

Abstract: This work investigates heat transfer and phase change during picosecond laser ablation of nickel. In this study, ablation of nickel is studied using a mode-locked 25 ps (FWHM) Nd:YAG laser. The threshold fluence for mass removal (ablation) is experimentally determined. Numerical calculations of the transient temperature distribution and kinetics of the solid-liquid and liquid-vapor phase change interfaces are performed. The results show that evaporation is negligible at the free surface, resulting in superheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…The thermal mechanisms of pulsed laser ablation include surface normal evaporation and homogeneous boiling, or phase explosion. During high power pulsed laser ablation, phase explosion could be an important ablation mechanism [1][2][3][4], which occurs when the temperature of a superheated liquid approaches the thermodynamic critical point, and the homogeneous nucleation rate is sufficiently large to generate a large amount of nuclei in a short period of time. Experiments showed that phase explosion indeed occurred during nanosecond pulsed laser ablation of a metal [2], and surface temperaturepressure relation could deviate from the commonly used equilibrium Clausius-Clapeyron relation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal mechanisms of pulsed laser ablation include surface normal evaporation and homogeneous boiling, or phase explosion. During high power pulsed laser ablation, phase explosion could be an important ablation mechanism [1][2][3][4], which occurs when the temperature of a superheated liquid approaches the thermodynamic critical point, and the homogeneous nucleation rate is sufficiently large to generate a large amount of nuclei in a short period of time. Experiments showed that phase explosion indeed occurred during nanosecond pulsed laser ablation of a metal [2], and surface temperaturepressure relation could deviate from the commonly used equilibrium Clausius-Clapeyron relation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Lm is the latent heat of fusion of Ni and S( r ,t) is the source term due to laser. The thermophysical or thermoelastic parameters that appear in the equations are derived using fitting techniques [22] or bibliographical records [29][30][31]. Fig.3a shows the spatial distribution of the lattice temperature at t=20ps after the material has been irradiated with two identical, 170fs, pulses at a fluence of 0.24J/cm 2 .…”
mentioning
confidence: 99%
“…In order to derive a comprehensive quantitative analysis of the morphological effects induced by radially polarized fs beams, we explore the dependence of the surface modification on the laser fluence and the number of incident pulses, assuming also the unique behaviour of g. While the fluence increase leads to a rise in the electron temperature Te (which is periodically modulated as a result of the initial SPP-originated periodical non-uniform energy deposition), the decrease of g with increasing Te leads to a delay of the heat transfer to the lattice via electron-phonon coupling with an increased efficiency of energy localization [31]. Therefore, the initial Te periodic distribution is expected to weaken substantially prior to heat transfer to the lattice, which will result to a less pronounced heat distribution to the lattice and eventually to a smaller ripple height (see for example Fig.4, for NP=100).…”
mentioning
confidence: 99%
“…Instead of direct material removal, however, the laser energy is also used for heating [2], melting [3] or assisting the other machining processes. In these scenarios the process is termed as laser assisting machining (LAM) [4].…”
Section: Introductionmentioning
confidence: 99%